2013
DOI: 10.4028/www.scientific.net/aef.8-9.259
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Technologies and Logistical Solutions for the Reuse of Demolished Concrete in the Construction of Cement Concrete Pavements

Abstract: Abstract. The paper presents the results and conclusions of investigations aiming to encourage the use of recycled materials, namely recycled aggregates (RA) and recycled steel fibers (RSF), in the construction of durable, economic and environmental friendly rigid pavements. To minimize and limit the negative effect of RA on the mechanical properties of cement concrete pavements, the research program considered both, development of technical solutions to improve the performance characteristics of RA particle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The thesis considered previous studies that also aimed at the recovery of demolished materials for the construction of durable, economical, and environmentally friendly rigid pavements. The results showed that the best combination was compressed concrete and recycled steel fibres (Muscalu, Andrei, Taranu, Budescu, Lungu, 2013). The problem that was most frequently found in the other studies examined was the reduction in mechanical strength of the mix composed of recycled aggregates; For this, it was useful to take into account the three hundred freeze-thaw cycles carried out by the group of researchers from the School of Civil Engineering and Architecture, Chongqing University of Science & Technology in China, who indicated that the freeze-thaw cycle strength of fine recycled aggregate is not related to the type of aggregate, but is determined by the water-cement ratio, the reduction of which is an effective way to improve its strength (Bu et al, 2022).…”
Section: State Of the Artmentioning
confidence: 99%
“…The thesis considered previous studies that also aimed at the recovery of demolished materials for the construction of durable, economical, and environmentally friendly rigid pavements. The results showed that the best combination was compressed concrete and recycled steel fibres (Muscalu, Andrei, Taranu, Budescu, Lungu, 2013). The problem that was most frequently found in the other studies examined was the reduction in mechanical strength of the mix composed of recycled aggregates; For this, it was useful to take into account the three hundred freeze-thaw cycles carried out by the group of researchers from the School of Civil Engineering and Architecture, Chongqing University of Science & Technology in China, who indicated that the freeze-thaw cycle strength of fine recycled aggregate is not related to the type of aggregate, but is determined by the water-cement ratio, the reduction of which is an effective way to improve its strength (Bu et al, 2022).…”
Section: State Of the Artmentioning
confidence: 99%
“…The results indicated that the CS value decreased from 135.5 to 130.2 MPa, but WRSF without any rubber attached to the surface increased the CS value from 135.5 to 141.3 MPa (4.3%). The increased mechanical bonding caused by frictional stress created by the corrugated surface and the geometry of the WRSF results in a rise in CS [109]. The WRSF provides resistance to cracks through a bridging effect and lateral crack resistance, resulting in the enhanced CS of CBCs [104,[110][111][112].…”
Section: Compressive Strengthmentioning
confidence: 99%